What a difference a day makes: differences in initial abstinence response during a smoking cessation attempt. (28th October 2016) - Piper, Megan E.; Vasilenko, Sara A.; Cook, Jessica W.; Lanza, Stephanie T.
Abstract: Aims: To (1) identify distinct classes of smokers based on quit day withdrawal symptoms and (2) explore the relations between withdrawal classes and demographics, tobacco dependence, treatment and smoking outcomes. Design: Secondary data analysis of participants ( n  = 1504) in a randomized double‐blind placebo‐controlled multi‐site smoking cessation trial who provided ecological momentary assessments of withdrawal symptoms on their quit day. Participants received smoking cessation counseling and were randomized to receive placebo or one of five active pharmacotherapies. Setting: Research offices in Madison and Milwaukee, Wisconsin, USA. Participants: Adult smokers ( n  = 1236; 58% female, 86% white), recruited from the community via advertisements, who abstained on their quit day. Measurements: Demographics and tobacco dependence were assessed at baseline and participants carried palmtop computers to record withdrawal symptoms (craving, negative affect, difficulty concentrating, hunger and anhedonia) on their quit day. Point‐prevalence abstinence and latency to relapse were assessed at 8 weeks and 6 months post‐quit. Findings: Latent class analysis identified four withdrawal classes [Akaike information criterion (AIC) = 70.09]: Moderate withdrawal (64% of sample), high craving–anhedonia (8% of sample), affective withdrawal (13% of sample) and hunger (15% of sample). The high craving–anhedonia class reported significantly higher dependence ( P  < 0.01), were less likely to have received combination nicotine replacement, reported lower week 8 abstinence rates and relapsed sooner than those in the moderate withdrawal class ( P  < 0.05). The affective withdrawal class reported higher levels of baseline negative affect and life‐time psychopathology ( P  < 0.05) and relapsed more quickly than the moderate withdrawal class ( P  < 0.01). Conclusions: While the majority of smokers report typical levels of withdrawal symptoms on their quit day, more than one‐third report extreme craving or extreme negative affective or extreme hunger responses to initial abstinence. These distinct quit‐day withdrawal symptom patterns are related to baseline characteristics, treatment and cessation success.